Dakwah Dalam Pemberdayaan Perempuan (Studi Materi dan Kegiatan Dakwah yang Dilaksanakan Muballighah di Banjarmasin, 2012) - Mudhi’ah, Norlaila (IAIN Antasari Banjarmasin, 2013)
This article discusses the mission of women empowerment, the material, and its activities that lead to improving womenâs quality in education, kesehatan, welfare, and leadership. Although most womenâs mission organization in Banjarmasin is generally held by women as the subject and object, only small numbers of materials that explore womenâs issues especially related to womenâs empowerment. Many of the materials covered are about worship, faith, and muamalah. The mission related to womenâs empowerment, orally, is delivered by women preachers who have ever involved, such as members of Parliament. Moreover, the mission of womenâs empowerment is practically run by an activist who is often called aâiyah/mubalighah or lector, or even moelem scholar.